Libraries through the ages - Lerner, Frederick Andrew, 1945-; Lerner, Frederick Andrew, 1945- (New York : Continuum, 1952)
A history of libraries throughout the world, from those of the ancient Sumerians and Egyptians to the comprehensive libraries of today.
1 The Fertile Crescent 13 -- 2 Greece and Rome 20 -- 3 Medieval Europe 28 -- 4 China and India 40 -- 5 The Islamic World 57 -- 6 The Printed Book 66 -- 7 Kings and Congressmen 74 -- 8 Colleges and Universities 82 -- 9 The People's Libraries 97 -- 10 Libraries for Young People 108 -- 11 Libraries at Work 115 -- 12 The Library of the Future 122.
Based on the author's The story of libraries.
Includes bibliographical references (p. [141]-142) and index.
Keywords: Libraries -- History -- Juvenile literature; Libraries -- History